Corruption and government causes, consequences, and reform - Rose Ackerman, Susan (New York Cambridge University Press, 1999)
Corruption is a worldwide phenomenon. Developing countries and those making a transition from socialism are particularly at risk. This book suggests how high levels of corruption limit investment and growth and lead to ineffective government. Corruption creates economic inefficiencies and inequities, but reforms are possible to reduce the material benefits from payoffs. Corruption is not just an economic problem, however; it is also intertwined with politics. Reform may require changes in both constitutional structures and the underlying relationship of the market and the state. Effective reform cannot occur unless both the international community and domestic political leaders support change.
Includes bibliographical references (p. 230-252) and indexes
Keywords: Political corruption